Salicylic acid-induced accumulation of biochemical components associated with resistance against Xanthomonas oryzae pv. oryzae in rice - Toan Le Thanh (Journal of Plant Interactions, 2017)
Seed treatment and foliar sprays of salicylic acid (SA) provided protection in rice against bacterial leaf blight (BLB) caused by bacterial Xanthomonas oryzae pv. oryzae (Xoo). Treatment of rice with exogenous SA reduced disease severity by more than 38%. Superoxide anion production and hypersensitive response increased approximately 28% and 110% at 6 and 48 h after Xoo inoculation, respectively, for plants treated with SA. Moreover, the Xoo in treated rice plants grew more slowly, resulting in a population that was half of that observed in the control. Fourier transform infrared spectroscopy analysis revealed that the higher ratios of 1233/1517, 1467/1517, and 1735/1517 cm−1 observed in treated rice suggested alteration of monomer composition of lignin and pectin in the rice cell wall. Exogenous SA-treated rice had more amide I β-sheet structure and lipids as shown by the peaks at 1629, 2851, and 1735 cm−1. These biochemical changes of rice treated with SA and inoculated with Xoo were related to primed resistance of the rice plants to BLB disease.